Axon deviation in the human lamina cribrosa. Issue 6 (1st June 1998) - Morgan, James E; Jeffery, Glen; Foss, Alexander J E
Abstract : AIMS: To examine the course taken by individual retinal ganglion cell axons through the human lamina cribrosa. METHODS: Retinal ganglion cell axons were labelled using the retrograde tracer horseradish peroxidase applied directly to the optic nerve in two normal human eyes removed during the course of treatment for extraocular disease. RESULTS: A majority of axons took a direct course through the lamina cribrosa but a significant minority, in the range 8–12%, deviated to pass between the cribrosal plates in both central and peripheral parts of the optic disc. CONCLUSIONS: It is postulated that these axons would be selectively vulnerable to compression of the lamina cribrosa in diseases such as glaucoma in which the intraocular pressure is increased.